Analysis of Educational Service Marketing Strategies in Increasing Prospective Students’ Interest during the New Student Admission Period (PMB) at LP3I Lampung - Shelma Anggi Zhafira; Desi Derina Yusda; Desmon Desmon (LPPPIPublishing, 2026)
This study aims to analyze the educational service marketing strategies implemented by LP3I Lampung to increase prospective students’ interest during the New Student Admission period (PPDB). The background of this research is the growing competition among educational institutions, which requires each institution to develop effective and innovative marketing strategies. This research employs a qualitative descriptive method, with data collected through interviews, observations, and documentation studies. The findings reveal that LP3I Lampung applies the 7Ps of service marketing mix, namely product, price, place, promotion, people, process, and physical evidence. The dominant promotional strategies include the use of social media, school seminars, direct visits, and scholarship programs. Service quality, competency-based curriculum, and partnerships with the industrial sector are the main attractions for prospective students. Supporting factors include institutional credibility and alumni networks, while the main challenge comes from competition with universities and other training institutions. The study concludes that an integrated marketing strategy has a positive impact on increasing student enrollment interest at LP3I Lampung. The analytical tool used is Miles & Huberman’s interactive model, which includes three main stages: (1) Data reduction, by selecting, focusing, and simplifying interview and observation results to highlight relevant information; (2) Data display, by presenting the findings in the form of narratives, tables, and matrices to identify patterns and relationships; and (3) Conclusion drawing/verification, by formulating key findings and verifying them for validity.